Strategies for keeping cow and calf together in six European countries - Gundersen, Sofia (2020)
The modern practice for dairy calf management is to separate the cow and calf a few hours after birth. That practice is highly debatable and consumers often oppose of it. There are several benefits for keeping cow and calf together for a longer period of time and letting the calf suckle. Calves develop a more advanced social behaviour, have a higher daily growth and develop less abnormal oral behaviours such as cross-sucking. Cows can get a better udder health and a longer lactation period when they are being suckled. Some studies have also shown that it can be economically benefi-cial to have a cow-calf contact system. This master’s thesis studied innovative sys-tems for keeping cow and calf together in six European countries. The participating countries were Austria, France, Germany, Italy, Sweden and Switzerland. A total of 119 farmers were interviewed over phone with a standardised questionnaire. The cri-teria for entering an interview was that the farmer had to keep cow and calf together for more than seven days. The results showed that there was a wide range on how long cow and calf were allowed to be together, from 7 to 305 days. The main system was rearing by dam and some farms had foster cows. Fishbone milking parlour was the most commonly used milking system. The overall herd size was similar to the average herd size of dairy farms in EU (2016: 33 dairy cows), but the farms ranged from 1 to 500 dairy cows. The farmers were asked to give their perception of cow and calf health and the overall answer was that it was better in systems allowing cow-calf contact for more than seven days. This thesis showed that there are active dairy farms using systems where cow and calf are kept together and that it is possible to implement a cow-calf contact system on a farm with a modern milking system. This thesis also showed that larger farms (> 36 cows) more frequently used a calf rearing system with foster cows or a mixed system (foster cow and dam), rather than only mother.